ANALISIS UNDANG-UNDANG NOMOR 2 TAHUN 2012 TENTANG PEMBERIAN GANTI RUGI ATAS PROYEK PENGADAAN TANAH UNTUK KEPENTINGAN UMUM PERSPEKTIF HUKUM ISLAM - Chamim Tohari (Hukum Islam, 2018)
This research focused to analyze arrangements about implementation of the loss subtitution gift for a land deliverance in the process of the land supplying which is attached in Indonesian‟s Contitution Number 2 Year 2012 in the perspective of Islamic Law. The problem which will answered in the research is about the arrangements is it according to the concept of the loss subtitution gift in Islamic law? The research is a normative law research library research type which is use a comparative analysis method as a method used to supply the answer of the problem in the research. The results of the research there are: First, in the perspective of fiqh problem in the research. The results of the research there are: First, in the perspective of fiqh importance reconstruction has been according to the concept of kafâlah in the conference and the loss substitution gift stage when agreement about the amount of the loss substitution reached . However in the next stage when the owner of land do not agree about amount of the loss substitution gift, the constitution has not been according to the concept ot kafâlah particularly, and the principles of the fiqh muamalah generally. Second, based on the fiqh siyasah perspective, the constitution can be concluded that it has been according to the principles of fiqh siyasah. Because the infra structure development for the general importance has been relevance to the maslahah of the citizen and the nation. Based on this argument, all of the citizen of Indonesia have to obey the constitution for the maslahah realization.